More than a token showing. - Blass, Anthony (Far Eastern Economic Review, 1994)
Part of a special section on U.K. investment in Asia. In April 1994, British entrepreneur Robert Madge established an international headquarters in Hong Kong, from which he hopes to exploit the growing regional market for so-called token ring technology. This software-based technology increases the processing power of individual PCs in a network, thus enhancing the system's speed and diminishing the need for costly mainframe computers and the high-paid technicians who look after them.